SimulaPed: A Serious Game for Pediatric and Neonatal Nursing Medication Dosage - Kohlrausch, André Luiz T.; Morales, Analucia S.; Sene Jr, Iwens (Companion Proceedings of the Brazilian Symposium on Computing Applied to Healthcare (SBCAS); 2025: Companion Proceedings of the 25th Brazilian Symposium on Computing Applied to Health, 2025)
This article presents the development of SimulaPed, a serious game designed to assist in teaching safety in medication administration in pediatric and neonatal nursing. The game proposes fictional clinical scenarios in which the player navigates through clinical cases and questions, receiving immediate feedback on correct answers and the consequences of errors. The efficacy evaluation was conducted using an initial prototype and sent to various professionals in the field, with preliminary results indicating that the game is a promising tool for enhancing students’ learning and confidence in the safe administration of medications.